An optimisation framework for Excel spreadsheet - Choy, Zhan Hao (Nanyang Technological University, 2024)
With ever-growing and fast-paced movements of goods and services brought about by globalisation, logistics and service distribution formed the backbone of matching goods and services to people’s needs. This brings about optimisation problems, with difficulties to decipher the best ways to maximise efficiency and minimise cost. This defines and relates to the problem of Travelling Salesman Problem and Vehicle Routing Problem. How can we deliver the goods and service supplies to match demand timely and correctly, while minimising cost, time and effort? This project aims to resolve and overcome those problem, bringing about low-cost methods to optimise the distribution problems, to cater especially for those small medium enterprises and companies. This solution will be proposed through integrating Python computing and Microsoft Excel Spreadsheet, which is commonly utilised as part of companies’ commercial applications.